Odpowiedzi

Najlepsza Odpowiedź!
2010-01-24T14:23:35+01:00
27(x-1/3y)(x+1/3y)-2(x-y)^2-2xy =
= 27(x²-1/9y²)-2(x²-2xy+y²)-2xy =
= 27x²-3y²-2x²+4xy-2y²-2xy =
= 25x²-5y²+2xy

x = 2
y = -4

25x²-5y²+2xy =
= 25*2² - 5*(-4)² + 2*2*(-4) =
= 25*4 - 5*16 + 4*(-4) =
= 100-80-16 =
= 4

1% z 4 = 0,01 * 4 = 0,04
2010-01-24T14:32:59+01:00
27(x^2-1/9y^2)-2(x^2-2xy+y^2)-2xy=
=27x^2-3y^2-2x^2+4xy-2y^2-2xy=
=25x^2-5y^2+2xy

a=2 b=-4
Rozumiem, że a=x, a b=y
25*2^2-5*(-4)^2+2*2*(-4)=
=25*4-5*16-16=
=100-80-16=4

4*1%=4*(1/100)=0,04